Climate Change, ecosystem impacts and systemic risk - Arnell,N; Jonsson,G; Oliver,T; Senapathi,D; Gambhir,A (2022)
This report highlights some of the vital dependencies of human societies on ecosystems, the damages that can occur from them as a result of climate change, and the steps required to better understand and characterise the systemic risks to societies that result from such climate change-driven ecosystem damages.